Surgical experiences with pulmonary hydatid cysts at Birendra hospital, Nepal - MJSBH, MJSBH (Medical Journal of Shree Birendra Hospital, 2006)
Surgical experiences with pulmonary hydatid cysts at Birendra hospital, Nepal